D-shaped configurations in FTU for testing liquid lithium limiter: Preliminary studies and experiments. (August 2017) - Ramogida, G.; Calabrò, G.; Crisanti, F.; Apicella, M.L.; Artaserse, G.; Bin, W.; Boncagni, L.; Brolatti, G.; Buratti, P.; Carlini, M.; Carnevale, D.; Costa, P.; et al.
Highlights: FTU can contribute to power exhaust studies with the actively Cooled liquid Lithium Limiter. D-shaped plasma with outer X-point close to the Li limiter could allow the access to H-mode. Installed ECRH heating should be adequate to exceed L-H power threshold with outer X-point. A predictive vertical position controller deals with VDE when elongation is greater than 1.17. A true in-vessel X-point can be achieved with a minor update of the poloidal coils system. Abstract: The feasibility of getting "D" shaped plasma configurations in FTU, with a possible X point close to the first wall, has been investigated with the aim of achieving an H-mode regime in this machine. This regime could allow both evaluating the thermal effects on the liquid lithium limiter due to the possible Edge Localized Modes and studying the L-H transition properties in low recycling conditions due to the presence of lithium.. An alternative design for the magnetic system in FTU has been also proposed, to realize an X-point inside the plasma chamber, close to the Liquid Lithium Limiter. Preliminary experiments with elongated configurations and limited ECRH additional heating power did not allowed approaching the L-H transition but they were used to develop a proper elongation control. This controller allowed guaranteeing the vertical stability in elongated configurations despite the reduced power available for the horizontal field coils in FTU. The elongation was stably keep over 1.2, while the lithium limiter was very close to the last close flux surface. Neither limiter damages nor plasma pollution were observed in these configurations. A possible alternative connection of the poloidal field coils in FTU is here proposed, with the aim of achieving a true X-point configuration with a magnetic single null well inside the plasma chamber and strike points on the lithium limiter. A preliminary assessment of this design allowed estimating the required power supply upgrade and showed its compatibility with the existing mechanical structure and cooling system, at least for plasmas with current up to 300 kA and flat-top duration up to 4 s.